2017
DOI: 10.3168/jds.2017-13210
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of lactating Holstein cows submitted to a Double-Ovsynch protocol and timed artificial insemination versus artificial insemination after synchronization of estrus at a similar day in milk range

Abstract: Our objective was to compare the AI submission rate and pregnancies per artificial insemination (P/AI) at first service of lactating Holstein cows submitted to a Double-Ovsynch protocol and timed artificial insemination (TAI) versus artificial insemination (AI) to a detected estrus after synchronization of estrus at a similar day in milk range. Lactating Holstein cows were randomly assigned to receive their first TAI after a Double-Ovsynch protocol (DO; n = 294) or to receive their first AI after a synchronize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 44 publications
2
31
1
8
Order By: Relevance
“…Serum progesterone concentrations after 7-days from last GnRH in each protocol was similar i.e., DOS; 8.68 ± 0.78 and OVS 8.19 ± 1.85 ng/mL (P>0.05). The suitability and successful induction of the DOS in various synchronization regimens has previously been reported in Holstein cows to improve the ovulation rate and fertility (Souza et al 2008,Herlihy et al 2012, Santos et al 2017. Similarly, the findings of our study support the hypothesis that by using DOS protocol pregnancy rate in crossbred dairy cows can be enhanced under subtropical conditions.…”
Section: Resultssupporting
confidence: 87%
“…Serum progesterone concentrations after 7-days from last GnRH in each protocol was similar i.e., DOS; 8.68 ± 0.78 and OVS 8.19 ± 1.85 ng/mL (P>0.05). The suitability and successful induction of the DOS in various synchronization regimens has previously been reported in Holstein cows to improve the ovulation rate and fertility (Souza et al 2008,Herlihy et al 2012, Santos et al 2017. Similarly, the findings of our study support the hypothesis that by using DOS protocol pregnancy rate in crossbred dairy cows can be enhanced under subtropical conditions.…”
Section: Resultssupporting
confidence: 87%
“…In the study by Neves et al (2012) the overall reproductive performance was found to be similar between management based on automated activity monitoring (AAM) and a synchronization program for TAI, including Ovsynch, Presynch or Co-Synch. Double-Ovsynch treatment appears to increase CR to the maximum currently attainable level (Souza et al, 2008;Herlihy et al, 2012;Neves et al, 2012;Santos et al, 2017). Hence our results are not consistent with Denis-Robichaud et al (2018) who reported improved CR if Double Ovsynch protocol was administered (36.3%) rather than application of the AAM system (32%).…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, a method used by many commercial farms to submit cows for insemination consists of synchronizing ovulation followed by timed AI (TAI; Pursley et al, 1995Pursley et al, , 1997. Benefits of TAI include insemination at a predetermined time regardless of expression and detection of estrus and the possibility of achieving similar or greater fertility than that of AI at detected estrus (Pursley et al, 1997;Santos et al, 2017). A major caveat of implementing TAI programs is the need to administer multiple hormonal treatments as intramuscular (IM) or subcutaneous injections.…”
mentioning
confidence: 99%